Strategi Pemecahan Masalah Pendidikan Agama Islam di Kampus Akademi Farmasi Dwi Farma Bukittinggi - Zul Efendi (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This study examines problem-solving strategies for Islamic religious education in pharmacy campus environments, motivated by the importance of Islamic education in shaping students' character, ethics, and morals, as well as the unique challenges of integrating Islamic values with modern pharmaceutical science. The main issues identified include lack of student interest and motivation, difficulties in integrating religious values with pharmacy materials, limited time and lesson allocations, and insufficient facilities supporting religious activities. The research aims to discover appropriate strategies to address these issues and enhance the effectiveness of Islamic education in pharmacy campuses. The findings reveal several key strategies that can be implemented, including: establishing binding regulations, organizing meetings with off-campus religious lecturers, coordinating with student affairs departments, combining suitable learning methods, increasing worship practices, strengthening basic religious understanding, creating engaging religious activities, and habituating Quran reading before lectures. The study's conclusion emphasizes the importance of implementing these strategies comprehensively and sustainably, with support from the entire academic community, to produce a young generation excelling in academics and possessing noble character based on Islamic values.